Canva AI Microsite-Based Media Development in Islamic Religious Education Learning at SMK Ma'arif 1 Metro - Hanafi Umar; Irhamudin; Kholida Nur; Choirudin; Adi Wijaya; Lutfi Fadilah; Syamsu Rizal (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to develop interactive learning media based on microsites using Canva AI Code Generator in Islamic Religious Education (PAI) learning at SMK Ma'arif 1 Metro. The study used the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate) combined with an effectiveness test through a one-group pretest–posttest design. The research subjects involved 25 grade X students. The research instruments included material expert validation sheets, media expert validation sheets, student response questionnaires, teacher response questionnaires, and learning outcome tests. Data were analyzed using the percentage of feasibility, paired t-test, and Normalized Gain (N-Gain). The results showed that the developed microsite media obtained a very valid category based on validation from material experts (95.71%) and media experts (83.68%). The practicality of the media was categorized as very practical based on student responses (83.02%) and teacher responses (86.67%). The effectiveness test showed a significant increase in student learning outcomes, with an average pretest score of 61.60 to 91.80 in the posttest (t = -8.557; p < 0.05). The N-Gain value of 0.76 is in the high category. These findings indicate that the Canva AI Code Generator-based microsite is valid, practical, and effective as a learning medium for Islamic Religious Education in vocational schools.